Social value of pathology: adapting primary health care to reduce stress and social anxiety in college students exposed to social distancing - Sava, Ionel N. (Frontiers in Psychology, 2023)
This article examined the impact of online education on the wellbeing and emotional health of college students. It considered the social value of stress and anxiety pathology as “normal” side effects throughout the COVID-19 lockdown. Factors appropriate for educational technology were selected and submitted for evaluation to a sample of 114 college students in a semi-structured questionnaire. This research found that educational content and delivery methods, as well as increased homework and time spent online, have potentially contributed to heightened levels of stress, depression, and social anxiety disorder among approximately one-third of students who have engaged in digital learning. The results also prove that young people were particularly susceptible to stress and social anxiety disorders during the lockdown, making them one of the most vulnerable social groups. To enhance the educational experience, several suggestions have been proposed, including adapting educational content, expanding Internet accessibility, providing appropriate homework, and adjusting schedules to accommodate students' educational capabilities. Voluntary routine mental health assessments of students, teachers, and staff and customized online counseling for vulnerable subjects are recommended as primary health care measures during online education.